Using role play technique and cue cards media to teach speaking for the eighth grade students of SMPN 13 Madiun - Eka Indah Sri Lestari (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
This study aims to determine and analyze (1) usingroleplay technique and cue cards media to teach speaking skills for the eighth grade students of SMPN 13 Madiun. (2) problems found in usingrole play technique and cue cards media to teach speaking skills for the eighth grade students of SMPN 13 Madiun. (3) solution given in usingrole play technique and cue cards media to teach speaking skills for the eighth grade students of SMPN 13 Madiun. The subjects of this study were 32 grade VIII students of SMPN 13 Madiun. The method used in data collection is the test method using observations, interview, and documentation. The analysis used in this research is the data condensation, displaying data, drawing and verifying conclusion. The results showed that (1) the implementation of using roleplay technique and cue cards media in teaching speaking consists of three phases: pre-activities, whilst activities, and post-activities. (2) The problems of the using roleplay technique and cue cards to teach speaking as follows: first, students felt that they were lack vocabulary and felt confused when they wanted to speak in English. Second, students still quite do not active in classroom because unprepared the material. Third, students still have low grammar so they have quiet difficult in make media cue cards. (3) The solutions to solve the problems in using cue cards media to teach speaking as follows : First is the teacher often invites students to speak use English to increase their vocabulary. The second is the teacher as a controller for students group and gives feedback.